Online Transportation in the City of Semarang (Socio-Economic Studies on Online Drivers) - Fahritsani, Husna; Rusdarti, Rusdarti; Martitah, Martitah (JESS (Journal of Educational Social Studies), 2022)
Transportation is the activity of transporting goods or passengers from one place to another. Transportation is very important because transportation is something that makes it easier for the general public to reach their goals. The study used a qualitative descriptive approach located in the city of Semarang. Research focuses on socio-economic studies of online drivers. Results of the study, online drivers show that most of them have secondary education. Monthly income range of Rp. 4,000,000,- (four million rupiah), being an online driver, although not an option, can improve the economic welfare of online drivers and their families, especially in meeting basic needs. To meet the needs of daily life, including the cost of children's education, it is done sparingly. This shows that there is a relationship between the level of education completed and the work they have, meaning that the higher a person's level of education will provide the possibility to get a better job.